AUDIT KOMUNIKASI LEMBAGA PEMERINTAH KECAMATAN TEMBALANG, KOTA SEMARANG - Yuliyanto, Muchamad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Communication plays important role in the operation of an organization. Communication is able to push or block the productivity of an organization. Tembalang district government as organization that provide services to the community need good communication climate that can push members’s productivity to service community. This research aimed to examine the communication models and patterns in Tembalang district government. This research is a qualitative descriptive study. The research data was collected through in-depth interviews. The results showed that communication pattern applied in the organization has been highly affected by communication pattern and leadership style of its chief as the highest commander. Openness, egality, transparent, and giving sample as the applied communication style by the chief has been pushing organization members to respond the communication in an instance or passing through some leader’s levels.